Spatial and Social Mobility in England and Wales: Moving Out to Move On? - Franz Buscha; Emma Gorman; Patrick Sturgis (Institute of Labor Economics (IZA), 2020)
Social mobility—the extent to which social and economic position in adulthood is facilitated or constrained by family origins—has taken an increasingly prominent role in public and policy discourse. Recent studies have documented that not only who your parents are, but also where you grow up, influences subsequent life chances. We bring these two concepts together to study trends in social mobility in England and Wales, in three post-war generations, using linked Decennial Census data. We estimate rates of occupational social class mobility by sex and region of origin. Our findings show considerable spatial variation in rates of absolute and relative mobility as well as how these have changed over time. While rates of upward mobility increased in every region between the mid-1950s and the early 1980s, this upward shift varied across different parts of the country, and tailed off for more recent cohorts. We also explore the role of domestic migration in understanding these temporal and spatial patterns, finding that those who stayed in their region of origin had lower rates of upward mobility compared to those who moved out, although this difference also narrowed over time. While policy discussion has focused almost entirely on national-level trends in social mobility, our results emphasise the need to also consider persistent spatial inequalities.
Keywords: J62; J61; J21; I24; I26; R12; 330; intergenerational mobility; social mobility; regional economics; spatial mobility